(untitled) (The University of Nairobi Journal of Language and Linguistics, 2025)
Gĩkũyũ has in-situ and ex-situ focus marking strategies. In the in-situ strategy, focus is marked on a constituent in its default syntactic position. In the ex-situ focus strategy, a constituent occurs at the front of a clause and gets attached to the morphemes nĩ- (‘is’) or ti- (‘is not’). This makes the morpheme nĩ- obligatory in an ex-situ focus construction; however, there is no consensus on its role. Whereas Clements (1984) and Schwarz (2007) see it as a focus marker, Bergvall (1987) sees it as an assertion marker. Consequently, the structure of the ex-situ clause has also been a subject of debate. In the literature, two main theoretical approaches compete in trying to explain it. The Focus Phrase Approach (Clements 1984) treats it as a mono-clausal construction, whereas the Cleft Analysis (Bergvall 1987) treats it as a bi-clausal one. The literature also fails to explain the motivation behind the ex-situ focus construction, particularly in cases where in-situ focus marking is also possible. For these reasons, the structure and the motivations behind ex-situ focus in Gĩkũyũ remain an open topic; hence, the interest of this paper. Using the Prominence Theory of Focus Realization (Büring 2010) to analyze data from sermons presented in the Gĩkũyũ language, this study concludes that the ex-situ focus construction in Gĩkũyũ is biclausal. Further, it demonstrates that the morphemes nĩ- and ti-, as used in the ex-situ focus constructions, are copula verbs which facilitate focus marking by allowing a focus-sensitive position after them. The study further establishes that the search for maximal prominence motivates the preference for the ex-situ focus construction in Gĩkũyũ. It also demonstrates that the “Prominence Constraint,” in the Prominence Theory of Focus Realization, requires parameterisation for it to more adequately account for the ex-situ focus construction in Gĩkũyũ.